TVP1022: A Novel Cardioprotective Drug Attenuates Left Ventricular Remodeling After Ischemia/Reperfusion in Pigs. Issue 2 (August 2015) - Malka, Assaf; Meerkin, David; Barac, Yaron D.; Malits, Eytan; Bachner-Hinenzon, Noa; Carasso, Shemy; Ertracht, Offir; Angel, Itzchak; Shofti, Rona; Youdim, Moussa; Abassi, Zaid; Binah, Ofer
Abstract : Background: The current cornerstone treatment of myocardial infarction (MI) is restoration of coronary blood flow by means of thrombolytic therapy or primary percutaneous coronary intervention. However, reperfusion of ischemic myocardium can actually provoke tissue damage, defined as "ischemia–reperfusion (I/R) injury." TVP1022 [the S-isomer of rasagiline (Azilect), FDA-approved anti-Parkinson's drug] was found to exert cardioprotective activities against various cardiac insults, such as chronic heart failure and I/R, in rat models. Therefore, we tested the hypothesis that TVP1022 will provide cardioprotection against I/R injury and post-MI remodeling in a pig model. Methods: For inducing MI, we used an I/R model of midleft anterior descending artery occlusion for 90 minutes followed by follow-up for 8 weeks in 18 farm pigs (9 pigs in each group, MI + TVP1022 or MI + Vehicle). Echocardiographic measurements were performed and cardiac scar size was calculated using histopathological methods. For fibrosis evaluation, we measured the interstitial collagen volume fraction in the remote noninfarcted tissue. Results: TVP1022 administration significantly decreased cardiac scar size, attenuated left ventricular dilation, and improved cardiac function assessed by segmental circumferential strain analysis. Furthermore, TVP1022 significantly reduced myocardial fibrosis 8 weeks post-MI. Conclusions: Collectively, these findings indicate that TVP1022 provides prominent cardioprotection against I/R injury and post-MI remodeling in this I/R pig model.